2014
DOI: 10.1038/nutd.2014.38
|View full text |Cite
|
Sign up to set email alerts
|

Altered levels of serum sphingomyelin and ceramide containing distinct acyl chains in young obese adults

Abstract: Objective:Recent studies indicate that sphingolipids, sphingomyelin (SM) and ceramide (Cer) are associated with the development of metabolic syndrome. However, detailed profiles of serum sphingolipids in the pathogenesis of this syndrome are lacking. Here we have investigated the relationship between the molecular species of sphingolipids in serum and the clinical features of metabolic syndrome, such as obesity, insulin resistance, fatty liver disease and atherogenic dyslipidemia.Subjects:We collected serum fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
104
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(126 citation statements)
references
References 34 publications
17
104
3
2
Order By: Relevance
“…We observed increased levels of plasma SM 18:0 during late gestation in preeclamptic patients which is in line with previous reports describing elevated levels of SM 18:0 in term plasma of early-onset preeclamptic patients [42] and as well as in human PE placentae when compared with control subjects [43]. Recent studies have demonstrated that serum elevation of this particular class of sphingomyelin positively correlates with parameters of insulin resistance and liver function in obese adults [44] and correlates with markers of NF-kB activation and thus markers of intracellular inflammation [44]. It is well-documented in the literature that increased high plasma sphingomyelin levels are associated with subclinical atherosclerosis and coronary artery disease [24].…”
Section: Discussionsupporting
confidence: 92%
“…We observed increased levels of plasma SM 18:0 during late gestation in preeclamptic patients which is in line with previous reports describing elevated levels of SM 18:0 in term plasma of early-onset preeclamptic patients [42] and as well as in human PE placentae when compared with control subjects [43]. Recent studies have demonstrated that serum elevation of this particular class of sphingomyelin positively correlates with parameters of insulin resistance and liver function in obese adults [44] and correlates with markers of NF-kB activation and thus markers of intracellular inflammation [44]. It is well-documented in the literature that increased high plasma sphingomyelin levels are associated with subclinical atherosclerosis and coronary artery disease [24].…”
Section: Discussionsupporting
confidence: 92%
“…Most noteworthy, however, was the observation that athletes had significantly less basal serum C18:0 sphingomyelin than T2D. There is reason to believe that C18:0 sphingomyelin is particularly deleterious for insulin sensitivity in humans (14,22) and may serve as novel biomarker in this regard. Furthermore, serum sphingomyelin decreased in recovery from exercise with a similar response in most species.…”
Section: Discussionmentioning
confidence: 92%
“…Metabolomic profiling has helped clarify this discrepancy by associating certain sphingomyelin species, rather than total concentration, with metabolic parameters. For example, sphingomyelin 18:0, 20:0, 22:0, and 24:0 were associated with higher BMI and lower insulin sensitivity (14,22), whereas serum sphingomyelin 16:1 was related to enhanced insulin sensitivity and lower risk for diabetes (10). Thus, like most lipids, sphingomyelins are heterogeneous and have different effects related to acyl chain composition.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the HOMA-IR also positively correlate with changes in the SM (d18:0/16:1). Hanamatsu et al [32] demonstrate that the high levels of serum SM species with distinct saturated acyl chains including C18:0 closely correlate with the HOMA-IR and BMI. These results suggest that BCAAs, aromatic amino acids, and SM, as observed in our study as L-leucine, L-phenylalanine, and SM (d18:0/16:1), are associated with the development of IR.…”
Section: Resultsmentioning
confidence: 99%